Biomechanical Comparison of Nitinol Compression Staples vs Fully Threaded Lag Screws for Talonavicular Arthrodesis Following 24-Hour Incubation at Body Temperature - Ashwin Garlapaty; James Cook DVM, PhD; Will Bezold BSME; Kyle M. Schweser MD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Other Introduction/Purpose: Arthrodesis of the talonavicular joint is indicated for injury- and arthritis-related pain. The standard treatment for talonavicular arthrodesis is lag screw fixation. Despite favorable results using lag screw fixation, it is associated with significant effects on foot biomechanical motion, and suboptimal complication rates. Nitinol staples have been used for talonavicular arthrodesis for their potential to address shortcomings of lag screw fixation. This study tested the null hypothesis that nitinol staples would not be significantly different from fully threaded lag screws based on biomechanical properties. Methods: Cadaveric feet (n=10) were acquired from 5 donors. Either nitinol staples or two cannulated lag screws were used to perform surgical arthrodesis of the talonavicular joint. Samples were incubated for 24-hours at 38°C, allowing for activation of the thermal nitinol compression properties. 38°C was chosen to mimic in vivo conditions. Biomechanical motion analysis was conducted. Specimens were loaded to 445N and held for 1 minute. A continuous compressive load of 445N was applied while cycling between plantarflexion to dorsiflexion for 10 cycles and then inversion to eversion for 10 cycles. Data were recorded along the X, Y, Z planes. Rotation data were recorded for roll, pitch, and yaw. Significant (p< 0.05) differences were determined. Results: No statistically significant differences in functional biomechanical testing properties were noted between nitinol compression staple fixation and lag screw fixation for talonavicular arthrodesis following 24 hours of incubation. Static compression, plantarflexion, dorsiflexion, inversion, and eversion testing resulted in nonsignificant translation in the X, Y, and Z planes, as well as nonsignificant rotation in roll, pitch, and yaw directions. Conclusion: Based on clinically relevant biomechanical properties measured during robotic testing, nitinol staples can be considered an appropriate option for talonavicular arthrodesis. Further work to assess long term outcomes of nitinol compression staples for talonavicular arthrodesis is currently ongoing. Biomechanical Data Mean translation and rotation for static and dynamic cyclical compression testing in plantarflexion, dorsiflexion, inversion, and eversion of the foot to assess talo- navicular arthrodesis fixation.